SERUM TRACE MINERALS VARIATION DURING PRE AND POST-PARTUM PERIOD IN NILI-RAVI BUFFALOES - M. S. Akhtar; A. A. Farooq; M. Mushtaq (Journal of Animal and Plant Sciences, 2009)
The present study was conducted with the objective to the iron, copper and zinc variations in serum of Nili-Ravi buffaloes during pre and post partum periods determine. The study was carried out on 35 pregnant Nili-Ravi buffaloes during June 2008 to October 2008 at Buffalo Research Institute, Pattoki, District Kasur. Blood samples were taken from these buffaloes during three, two and one week before parturition, at the time of parturition and then one, two and three weeks after parturition. Serum iron, copper and zinc were determined on Atomic Absorption Spectrophotometer. The mean serum iron and copper concentration differed significantly (P<0.05) among different groups. There was decreasing tendency of iron concentration towards parturition. The copper concentration was found significantly higher (P<0.05) at the day of parturition and it increased thereafter significantly (P<0.05) following three weeks. The serum zinc concentrations increased significantly (P<0.05) among last three weeks before parturition. There was non-significant (P>0.05) decrease in zinc concentration between 1st and 2nd week after parturition where as a significant increased (P<0.05) in zinc concentration took place during 3rd week after parturition. Serum zinc concentrations also dropped at the day of parturition.
Keywords: Nili-Ravi buffalo; parturition; serum; iron; copper; zinc.